Albania : Fourth Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility, Review Under the Extended Arrangement, and Financing Assurances Review; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Albania. (IMF Staff Country Reports; Country Report, 2008)
The main challenges for this review were to further redress long-running problems in the energy sector and to balance fiscal policy requirements for development spending with macroeconomic stability. The financial position of the state-owned electricity company (KESH) deteriorated significantly more than anticipated. The authorities have adopted a two-pronged solution to the electricity crisis. The authorities are prioritizing the strengthening of regulation to assure financial stability in a rapidly maturing financial system. The proposed conditionality for the Fifth Review is consistent with program goals, and the program is fully financed.